ANALISIS TRANSPARANSI PARTISIPASI DAN AKUNTANBILITAS PENGELOLAAN DANA DESA: Studi Kasus pada Desa Sako Kecamatan Pangean Kabupaten Kuantan Singingi Provinsi Riau Tahun Anggaran 2018 - Alwindria, Yoga; Taufik, Taufeni; Azlina, Nur (School of Accountancy, University of Agung Podomoro, 2019)
This study aims to analyze the management of the Village Fund in Sako Village. It alsoanalyzes themechanism of transparency, participation and accountability in the management of the Sako VillageFund. Last, itanalyzes the guidance and supervision procedures for managing the Sako VillageFund.This type of research is a qualitative study and uses a comparative descriptive approach. In thisresearch, the researcher describes Transparency, Participation and Accountability of Sako Villagefinancial management which includes planning, implementation, administration, reporting,accountability, guidance and supervision of village financial management and comparativecompliance with Law Number 6 of 2014 and Permendagri Number 20 of 2018 .The results showed thatin general the management of village funds in Sako Village from the planning, implementation,administration, reporting, and accountability stages can be said to be Transparent, Participatory, andAccountable. Although at each stage there are still small notes that become homework for the villagegovernment to be improved for the better. The training carried out by the Riau Provincial Governmentand Kuantan Singingi Regency can be said to be very good.